Sintesis dan Uji Aktivitas Anti-inflamasi Senyawa 2â€Hidroksiâ€Nâ€(Piridinâ€2â€il)Benzamida Tersubstitusi Basa Mannich Morfolin dan N-Metilpiperazin - Hayun Hayun; Catur Jatmika; Gadis Anggraini (Jurnal Penelitian Pendidikan IPA, 2023)
Salicylic acid is a naturally active substance known to have anti-inflammatory and antioxidant activity, but it has side effects in the gastrointestinal tract. The modification of its carboxylic groups into amide derivatives can be a solution to overcome its weakness. This study synthesized salicylamide analogs, 2-hydroxy-N-(pyridine-2-yl)benzamide (1) and, its Mannich base derivatives. The synthesized compounds (2a-b) showed anti-inflammatory activity based on an in-vitro anti-inflammatory activity test using the inhibition protein denaturation method. The IC50 obtained was in the range of 0.121-0.145 mM. The potency was lower than piroxicam used as a standard compound (IC50 = 0.0073 mM). The molecular docking result shows that the ratio of COX-2/COX-1 binding affinity and ligand interaction of all synthesized compounds were not COX-2 selective.